Accession of Sulphate Sulphur through Precipitation in Arid and Semi Arid Areas of Rajasthan - Aggarwal, R K (Annals of Arid Zone, 2016)
The concentration of So4-S in rainwater and its accession were studied during 1976 and 1977 of five stations of Rajasthan having an annual rainfall ranging from 215 to 613 mm. The mean annual concentration of So{-S ranged from 0.75 to 1.56 ppm, maximum being in Jaisalmer. Although the average concentration of different stations indicated the highest value for June, the peak concentration during a month varied at different stations. The annual accession of So4-S added (kg/ha) was found to be highly correlated with the amount of rainfall received (r=0.65, P